Tinjauan Hukum Efektifitas Kedudukan dan Kewenangan Pemerintah Daerah Terhadap Izin Pengelolaan Lingkungan - Warong, Robert Nicolas; Musa, Altje Agustin; Lumintang, Djefry Welly (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
This study aims to analyze the effectiveness of the position and authority of local governments in granting environmental management permits based on applicable laws and regulations. The research method used is normative with a statute approach and conceptual approach. The results of the study indicate that although the authority of local governments in environmental management has been regulated in various regulations, there are various obstacles in its implementation, such as overlapping policies, limited resources, and lack of coordination between the central and regional governments. Therefore, it is necessary to strengthen institutional capacity, harmonize policies, and increase community participation in the environmental licensing process in order to achieve sustainable development goals.